Peculiarities of Linguistic Analysis of the Text as a Language Learning Strategy - Kosenko, Anna; Bloshchynskyi, Ihor; Mishchynska, Iryna; Pasichnyk, Nataliia; Plavutska, Olga; Zakordonets, Nataliia; Hotsa, Nataliia (My University, 2021)
Linguistic analysis of the text is viewed as a language learning strategy in conditions of distance learning as well as in the process of regular classes. The results of the study conducted during the emergency (the quarantine) are presented in the article. The peculiarities of linguistic analysis of the text as a language learning strategy are highlighted in the article. Principles and methods of linguistic analysis of the text are considered in the study. The scheme of linguistic analysis of the text has been a key feature of the course in its application to varieties of texts according to their stylistic features. The mechanisms leading to realizing the process of linguistic education by its participants applying the language learning strategy are clarified. They consist in the deliberate combination of face-to-face and online learning activities providing for presentation of theoretical material as in the form of lectures as in independent and individual work of students. The experience of applying the course Basics of Linguistic Analysis in the process of linguistic education are generalized due to thorough choice of methodology in the process of presenting the material, conducting practical classes and carrying out control of the results of learning throughout the course. The prospects of professional development of future philologists by means of the linguistic analysis of the text are presented in the article.
Keywords: educational platforms, language learning strategy, linguistic analysis, methods and techniques of linguistic analysis